AI Speaks Your Language: Revolutionary Digital Coaching for EFL Learners’ Pronunciation - Donal Tampubolon; Reli Handayani; Mukhlash Abrar (Yayasan Visi Intan Permata, 2025)
The current study aims to find out the EFL learners’ major problems in pronouncing words of English and to explore the potential of AI technologies especially Google Pronunciation as a supportive tool for pronunciation improvement in secondary school settings. It measures the effectiveness of the tool in improving their pronunciation based on the class observation, pre- and post-assessment outcomes and according to the students’ perceptions. The study comprised 6 secondary high school students covering 2 low performers, 2 mediocre performers, and 2 high performers at English Club in one of the schools in Jambi, Indonesia. The participants were intentionally nominated based on their availability and readiness to provide recorded answers for the research purposes. A qualitative-descriptive research method was employed through a deep-interview to examine their major difficulties in pronunciations and their perspectives toward the tool. The results show that the learners’ chief pronunciation difficulties are both in segmental and suprasegmental features namely the sounds of /θ/ and /ð/, past simple sounds, and also stressed syllables. Their overall perceptions towards the use of the tool own more positive impacts as their pronunciation improves. Despite its effectiveness, the instrument is suggested to be used only for basic or standard pronunciation learning. For being natural in English pronunciation, the tool cannot perform much better than human teachers because it has limited accents and its phones sound too formal. Additionally, the tool is expected to advance the technology's adaptability to diverse accents and linguistic backgrounds, ensuring more inclusive and equitable learning experiences for all EFL learners.